Antigenic Properties and Virulence Among Mammalian Tubercle Bacilli - Mudd, Stuart; Furth, Jacob (The Journal of immunology (1950), 1927)
The human and bovine varieties of Mycobacterium tuberculosis, although possessing characteristic differences in pathogenic and cultural characters, have been shown to be antigenically similar. Nevertheless it has seemed of interest to select certain human and bovine strains which in respect to virulence are atypical and subject these to serological study by a greater diversity of method than has been brought to bear on this problem heretofore. The antigenic properties of five strains of mammalian tubercle bacilli described as avirulent are in this communication compared with those of a human strain of low virulence, H37, and a bovine strain of high virulence, Bovine C. It is found that strains differing profoundly in virulence may show similar serological behavior even when tested with the aid of sensitive adsorption methods. Thus the avirulent strains B.C.G. and R1, and two cultures of H37 were not differentiated antigenically from the virulent strain Bovine C; on the other hand, the same methods served to differentiate Bovine III and the saprophytic “Koch” strain from the virulent organism.